Recovery of Ag, Cu, Ni and Fe from the nitrate leach liquor of waste ICs. (1st November 2020) - Panda, Rekha; Jha, Manis Kumar; Pathak, Devendra Deo; Gupta, Rajesh
Highlights: Novel flow-sheet to recover Ag, Cu, Ni and Fe from leach liquor of ICs. Process consists of precipitation, solvent extraction and evaporation. ICs are promising secondary resource to recover precious metals. Abstract: Novel and simple flow-sheet has been reported to process integrated circuits (ICs) for effective recovery of metals. The depopulated ICs from waste PCBs were pulverised, beneficiated and leached in nitric acid. From the nitrate leach liquor, Fe was removed at pH 3.5, temperature 60 °C and air sparging. Subsequently, 99.99% Ag was precipitated as AgCl using 5% NaCl in mixing time 10 min. Further, 99.99% Cu was extracted from the filtrate using 20% LIX 984 N along with 2% isodecanol (ID) diluted in kerosene at pH 2.97, organic to aqueous phase ratio 1 in 10 min, leaving Ni in the raffinate. From the obtained pure solutions, salts of Cu and Ni could be produced using evaporation technique. The developed hydrometallurgical process flow-sheet to recover valuables from the nitrate leach liquor of waste ICs has the potential to be commercialised after pilot/ scale-up trial validations.